(untitled) (Research, Society and Development, 2021)
Objective: To verify the prevalence, risks, and factors that lead to self-medication, through an integrative literature review, searching for scientific studies in the central academic databases: Academic Google, Scielo, Medline, PubMed, and Redib. Methods: The literature review was conducted in October 2021, using the descriptors "Self-medication", "Pandemia", "COVID-19", "risks", and "prevalence". Results: After using the inclusion and exclusion criteria, twelve articles were obtained for this analysis. They showed that the population did seek self-medication as a means of a quick and easy solution to the disease, as it is lethal and has considerable morbidity. Another justification for the use of self-medication was the mistaken preventive purpose, given the lack of scientific evidence on the treatment and/or prevention of COVID-19. Conclusion: Based on the results presented, it is highlighted that it is of great importance to carry out more studies that assess the indiscriminate use of drugs used in the treatment and/or prevention of the disease, and the importance of the pharmacist professional and the multidisciplinary team in providing guidance is also highlighted and promoting the rational use of medicines during the COVID-19 pandemic.